Eksoterisme Tafsir Ishari: Telaah Epistemologi Tafsir Al-Jilani - Sansan Ziaul Haq (JOURNAL OF QUR'AN AND HADITH STUDIES, 2015)
Abstract This article concludes that the sufistic interpretation of al-Ji>la>ni> is in harmony with the principle of textual interpretation. In the process of isha>ri> interpretation, the dialectics between elements of textuality and spirituality makes the text have a literal-objective meaning as well a moral-spiritual significance. This study shows that the interpretation of al-Ji>la>ni> is literal, because it relies in textual meaning, and at the same time is spiritual, in the sense that the meaning also reaches spiritual outcrop. This study is based on interpretive method, with the hermeneutic and sufistic psychology approach. Abstrak Artikel ini menyimpulkan bahwa penafsiran sufistik al-Ji>la>ni> selaras dengan prinsip tekstualitas penafsiran. Dalam proses penafsiran isha>ri>, dialektika antara unsur tekstualitas dan spiritualitas menjadikan teks memiliki makna literal-objektif’ sekaligus signifikansi moral-spiritual. Penelitian ini menunjukan bahwa interpretasi al-Ji>la>ni> bersifat literal, karena mengimani makna tekstual, sekaligus bersifat spiritual, dalam arti bahwa pemaknaan juga menjangkau singkapan spiritual. Dalam melakukan kajian ini, penulis menggunakan metode interpretatif, dengan pendekatan hermeneutika dan psikologi sufistik. Keywords: Penafsiran isha>ri>, Makna tekstual, Signifikansi Moral-Spiritual.